2020
DOI: 10.1039/d0sc00741b
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced SNP-sensing using DNA-templated reactions through confined hybridization of minimal substrates (CHOMS)

Abstract: Confined hybridization of a minimal substrate: striking the right balance between specificity and turnover

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 65 publications
1
14
0
Order By: Relevance
“…21 The faster reaction for the second may be explained by additional base stacking interaction between pegIF and DpegH1, mediated by the formation of a pegIF:pegH2 duplex. [35][36][37] These results are consistent with previous PAGE results, which showed that some of the initiator remained unreacted when using a stoichiometric ratio of reagents (Fig. 2B, lane H1 + H2 + 1 eq.…”
Section: Resultssupporting
confidence: 92%
“…21 The faster reaction for the second may be explained by additional base stacking interaction between pegIF and DpegH1, mediated by the formation of a pegIF:pegH2 duplex. [35][36][37] These results are consistent with previous PAGE results, which showed that some of the initiator remained unreacted when using a stoichiometric ratio of reagents (Fig. 2B, lane H1 + H2 + 1 eq.…”
Section: Resultssupporting
confidence: 92%
“…The photo‐excited catalyst is reduced (SET with sodium ascorbate or NADPH) followed by a SET with the pyridinium moiety ( Figure 4 ,A ). This reaction was extended to immolative linkers to cage phenols and amines in vitro and in cellulo ( Figure 4 ,B ) [42,44,48–51] . Notably, the reduction of pyridinium‐based immolative linkers proved to be much faster than an azide‐based linker [48] .…”
Section: Click and Clip The Backbone Of Chemical Biologymentioning
confidence: 99%
“…This reaction was extended to immolative linkers to cage phenols and amines in vitro and in cellulo (Figure 4,B). [42,44,[48][49][50][51] Notably, the reduction of pyridinium-based immolative linkers proved to be much faster than an azide-based linker. [48] In further developments, it was shown that bioluminescence could be used for the photoexcitation of the ruthenium catalyst, leading to the development of semi-synthetic protein sensor that responds to an analyte with a photocatalyzed drug uncaging (Figure 4,D).…”
Section: Photoreductive Clips and Clicksmentioning
confidence: 99%
“…Inspired by this remarkable achievement, a pair of Ru-photocatalysts and pyridinium linkers has been further utilized to design various nucleic acid-sensing techniques for the detection of miRNA [ 82 , 83 ], double-stranded RNA [ 84 ], and single nucleotide polymorphism (SNP) [ 85 ].…”
Section: Chemical Bond Photocleavage Of Nucleic Acidsmentioning
confidence: 99%